2017
DOI: 10.18685/ejmr(6)2_ejmr-17-012
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Epidural anaesthesia using lidocaine with Adrenaline on Hemato-biochemical responses in pregnant West African Dwarf goats

Abstract: Epidural anesthesia is commonly utilized in veterinary medicine to allow diagnostic, obstetrical, and surgical interventions caudal to the umbilicus in the perineal region of large animal. Addition of a vasoconstrictor to a local anesthetic has been shown to have several beneficial effects. This study was carried out to investigate the effects of lidocaine with epinephrine on physiological, haematological and biochemical parameters in pregnant West African dwarf goats. Four healthy pregnant goats were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…In study on epidural anesthesia using lidocaine, [10] reported that the decrease in hematological profile values including erythrocytes, hemoglobin, hematocrit, neutrophils and platelets after epidural anesthesia may be due to fluid shifting from the extravascular to the intravascular compartment to compensate for normal cardiac output. It also reports an increase in lymphocyte content compared to reference standards.…”
Section: Discussionmentioning
confidence: 99%
“…In study on epidural anesthesia using lidocaine, [10] reported that the decrease in hematological profile values including erythrocytes, hemoglobin, hematocrit, neutrophils and platelets after epidural anesthesia may be due to fluid shifting from the extravascular to the intravascular compartment to compensate for normal cardiac output. It also reports an increase in lymphocyte content compared to reference standards.…”
Section: Discussionmentioning
confidence: 99%